2021
DOI: 10.1002/lsm.23377
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Outcomes of Focused Heating of the Skin by a Long‐Pulsed 1064 nm Laser with an Integrated Scanner, Infrared Thermal Guidance, and Optical Coherence Tomography

Abstract: Background and Objective: Long-term benefits can be predicted by the incorporation of more intelligent systems in lasers and other devices. Such systems can produce more reliable zones of thermal injury when used in association with non-invasive monitoring and precise laser energy delivery. The more classical endpoint of tumor destruction with radiofrequency or long-pulsed (LP) 1064 nm laser is the non-specific appearance of tissue graying and tissue contraction. Herein we discuss combining non-invasive LP 106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The Nd:YAG laser is especially helpful in clearing pigmented lesions and removing tattoos due to deep penetration and good absorbance by residual pigment. This deep penetration also allows the Nd:YAG laser to excel at clearing BCCs due to selective targeting and destruction of vascular structures 8,10 . Prior studies, using aggressive laser parameters, reported effective treatment of BCCs 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Nd:YAG laser is especially helpful in clearing pigmented lesions and removing tattoos due to deep penetration and good absorbance by residual pigment. This deep penetration also allows the Nd:YAG laser to excel at clearing BCCs due to selective targeting and destruction of vascular structures 8,10 . Prior studies, using aggressive laser parameters, reported effective treatment of BCCs 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This deep penetration also allows the Nd:YAG laser to excel at clearing BCCs due to selective targeting and destruction of vascular structures. 8,10 Prior studies, using aggressive laser parameters, reported effective treatment of BCCs. 11 Herein, we examine the efficacy of less-destructive protocols while utilizing noninvasive imaging to improve cosmetic outcome and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…As an important part of the optical fiber communication system, the photodetector is a component that converts optical signals into electrical signals. It is widely applied in optical communication 12 , laser guidance 19 , biosensing 20 , etc. If the transparent electrode is replaced from the traditional ITO to our FIRTC, the applicable band of the photodetector can be complemented to far-infrared region, which will promote the development of far-infrared search and guidance technology.…”
Section: Resultsmentioning
confidence: 99%
“…Although TC in the visible, near-infrared, and mid-infrared bands have been developed, TC in the far-infrared band have not been designed. This greatly limits the development of far-infrared electromagnetic shielding 13 , 14 , infrared thermal camouflage 15 , photo detection 16 19 , biosensing 20 technologies, and other fields. Therefore, we focus on far-infrared transparent conductors.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated excellent control of skin tissue temperature using an integrated FLIR imaging system in normal skin with a LP Nd:YAG 1064nm laser, and defined optimal time and temperature parameters to impact skin tissue responses 3 . Outcomes were defined clinically and by dynamic OCT both to recognize incipient or frank blistering and necrosis, and assess tissue blood flow.…”
Section: Introductionmentioning
confidence: 99%